Sintering mechanisms of ZrO2 center dot MgO with addition of TiO2 and CuO - Nasar, R. S.; Cerqueira, M.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2004)
Substitutions of Ti and Cu in ZrO2.MgO (Z), cause transformation from monoclinic (m) to cubic (c) and tetragonal (t). According to the vacancy model and solid Solution formation models, neither CuO nor TiO2 cause zirconia stabilization, which derives front other phenomena. Data analysis by TMA using the CRH (constant rate of heating) method shows a solid state reaction of ZrO2.MgO.TiO2 (Z.TiO2) demonstrating a dominant mechanism of volume diffusion (n = 1). However, the sintering of ZrO2.MgO.CuO (Z.CuO) shows a viscous flow mechanism (n = 0), a similar phenomena to that of by sintering of glass. Transformations, such as: CuO to Cu2O at 1000 degreesC, ZrO2 (m) to ZrO2 (t) at 1100 degreesC and Cu2O (s) to Cu2O (l) at 1230 degreesC cause successive rearrangements of microstructure inside of region I (sintering process) and lead to interpretation errors when the Bannister equation is used. (C) 2003 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: sintering; ZrO2; MgO; zirconia stabilization